The Influence of Workload Factors, Work Stress and Health Personnel Competency on the Implementation of Hospital Occupational Safety and Health Management Systems (SMK3RS) - Alfian Yoga Wiratna; Nway Eint Chei (Journal Of Nursing Practice, 2022)
Background: Accident prevention in the workplace cannot be separated from the influence of behavior and application by health workers in its implementation which prioritizes the interests of patient safety. The behavior and abilities of health workers play an important role in the implementation of patient safety. Several factors that influence the behavior of nurses in implementing the Hospital Occupational Health and Safety Management System (SMK3RS) are influenced by motivation, perceptions, attitudes, organizational culture, knowledge and experience. Purpose: The purpose of this study was to determine and analyze how the description influence and relationship between workload, work stress and implementation of Hospital Occupational Health and Safety Management System (SMK3RS) at Lira Medika Hospital Karawang. Methods: The sampling technique used is purposive sampling with a total sample of 100 people. This type of research is descriptive verification research. The statistical instrument used is regression analysis using validity, reliability, normality tests. Results: An influence of workload, work stress and competence on the assessment of the implementation of Hospital Occupational Health and Safety Management System (SMK3RS) by 19.05% because the rest is influenced by other variables or factors such as training, education level, motivation, leadership and others. Conclusion: Based on the results of the study, it appears that the workload parameters have no effect on the implementation of Hospital Occupational Health and Safety Management System (SMK3RS) for Medical Service/Supporting Staff at Lira Medika Hospital. Meanwhile, the direct effect is work stress and work competence.